An Investigation of Thai High School Students’ English Language Learning Problems - Than Thamajaree; Amporn Sa-ngiamwibool (Bandar Lampung University (UBL), 2014)
A way to improve English language teaching is an investigation of students’ English language problems. This study therefore explored Thai high school students’ English language learning problems. This was a case study, employing a survey design and using a questionnaire as instrument for data collection. The subjects were 104 high school students in Lampang Province, Thailand. The results of this study revealed the following findings. On listening, the students had difficulty in class discussion in English. On speaking, they had trouble with asking questions in English in the classroom. On reading, they could not understand English idioms. On writing, they were unable to finish essay writing within a limited time. On sociocultural perspectives on second language learning, they lacked opportunity to spend time associate with native speakers. On international communication barriers, on oral presentation for a lesson assignment, they rehearsed it only 2-3 times to prepare themselves. Lastly, of all language learning tasks, the most problematic English task was writing. This study is a puzzle to the whole picture. Future inquiry should replicate this study to see the whole picture of this issue.